Youth created media on the climate crisis hear our voices - Beach, Richard ca. 20./21. Jhr; Smith, Blaine E. (Routledge, Taylor & Francis Group, 2024)
This timely book provides effective methods and authentic examples of teaching about climate change through digital and multimodal media production in the English Language Arts classroom. The chapters in this edited volume demonstrate the benefits of addressing climate change in the classroom through innovative media production and cover a range of different types of media, including video/digital storytelling, social media, art, music, and writing, with rich resources for instruction in every chapter.Through the engaging ideas and strategies, the contributors equip educators with the critical tools for supporting students’ media production. In so doing, they offer new perspectives on how students can employ media and production techniques to critique the status quo, call for change, and acquire new literacy skills. As the effects of the climate crisis become increasingly visible to the youth population, this book helps foster and support youth agency and activism. Youth Media Creation on the Climate Change Crisis: Hear Our Voices is a necessary text for students, preservice teachers, and educators in literacy education, media studies, social and environmental studies, and STEM education.The eBook+ version of the text features embedded audio and video components as well as interactive links to reflect the multimodal nature of students’ work, spotlighting how youth media production supports the development of students’ critical literacy skills and shapes their voices and identities
Youth Climate Contributors List  Introduction: The Need for this Book  Section I. Justifying the Pedagogical Value of Media Production to Address the Climate Crisis  1. "We Are Nature Defending Itself": Universal Climate Literacy DIY with Youth Media Productions and Engagement  2. Centering Utopia: Fostering Youth Climate Change Education by Exploring and Envisioning Hopeful Future  3. General Ecology and Speculative Pedagogies: Youth Digital Media Practices for Climate Justice  4. Integrating Community-Based Participatory Research Approaches with Climate Justice Digital Media Projects  Section II. Engaging Students in Imaginative and Critical Thinking Through Media Production  5. "Our Story Will be the Future": A Learner-centered Approach to Support Digital Multimodal Composing about the Climate Crisis  6. "Listen, There, To the Way the Real World Thinks in Me"—Cultivating an Empathic Imagination to Support Students’ Visual Stories that Address the Climate Crisis  7. Addressing Climate Change and Sustainable Energy Futures Through Creative Music Engagement  8. Fostering Proactive Ecological Identity of Youth Through Social Media  Section III: Providing Students With Media Production Methods To Achieve Audience Uptake To Exact Change  9. Climate Writing Across Media: Scribing New Stories to Live By  10. The Long Haul: Three Decades of Teaching Student Documentary Action Research for Environmental and Climate Justice  11. Resilient by Youth Engagement: The Alameda Creek Atlas  12. Building Youth Voices: Media Created by Youth, For Youth
Keywords: Klimakatastrophe; Englischunterricht; Medienherstellung; Aufsatzsammlung